Censorship: Internet partially restored; social media still blocked (Bangladesh) - Voidly (2024)
CRITICAL severity censorship detected in Bangladesh. Confidence: 75%. Data sourced from CensoredPlanet.
Censorship Incident ID: BD-2024-0001
Keywords: censorship; BD; censorship; critical